Interlamellar Autogenous Tarsal Graft for the Correction of Lower Eyelid Trichiasis Associated With Eyelid Margin Thinning. Issue 6 (November 2018) - Cruz, Antonio A. V.; Garcez, Cecilia; Duarte, Ana; Akaishi, Patricia M. S.
Abstract : Purpose: To evaluate the use of autogenous tarsal graft for surgical correction of lower eyelid trichiasis associated with eyelid thinning. Methods: A total of 23 eyelids of 19 consecutive patients with trichiasis were operated with a variant of the Van Millingen procedure. The surgery consisted of interposing a 3-mm high fragment of autogenous ipsilateral upper eyelid tarsus corresponding to the trichiasis segment between the pretarsal anterior lamella and the lower tarsal plate. Preoperative assessment included quantification of eyelid thickness on the midpoint of the segment with trichiasis, biomicroscopy of the eyelid margin and location of the trichiasis. All patients were examined at 1, 3, 6, and 12 months after surgery. Eyelid thickness was measured at 1 month and 12 months of follow up. Results: Preoperatively the mean thickness of the eyelid margin was 0.99 mm ± 0.06 standard error. One month postoperatively eyelid thickness increased to 2.08 ± 0.28 standard error, decreasing over time to reach 1. 48 mm ± 0.18 standard error 1 year after surgery, a value that did not differ from that of the control group. Small granulomas were diagnosed only in the early phases of the postoperative period. Trichiasis recurrence was seen in just 1 eyelid. Isolated abnormal lashes lateral or medial to the graft were present in 5 eyelids at the end of the study. Conclusions: Autogenous tarsal grafts placed parallel to the lower tarsus are a good option both to correct misdirected eyelashes and to restore normal lower eyelid thickness. Abstract : Lower eyelid trichiasis associated with eyelid thinning can be managed with an interlamellar autogenous tarsal graft.